Inhibition of Interleukin‐6/glycoprotein 130 signalling by Bazedoxifene ameliorates cardiac remodelling in pressure overload mice. Issue 8 (12th March 2020) - Shi, Wei; Ma, Haiyan; Liu, Tianshu; Yan, Dan; Luo, Pengcheng; Zhai, Maocai; Tao, Jingwen; Huo, Shengqi; Guo, Junyi; Li, Chenglong; Lin, Jiayuh; Zhang, Cuntai; et al.
Abstract: The role of IL‐6 signalling in hypertensive heart disease and its sequelae is controversial. Our group demonstrated that Bazedoxifene suppressed IL‐6/gp130 signalling in cancer cells but its effect on myocardial pathology induced by pressure overload is still unknown. We explored whether Bazedoxifene could confer benefits in wild‐type C57BL/6J mice suffering from transverse aortic constriction (TAC) and the potential mechanisms in H9c2 myoblasts. Mice were randomized into three groups (Sham, TAC, TAC+Bazedoxifene, n = 10). Morphological and histological observations suggested TAC aggravated myocardial remodelling while long‐term intake of Bazedoxifene (5 mg/kg, intragastric) attenuated pressure overload‐induced pathology. Echocardiographic results indicated Bazedoxifene rescued cardiac function in part. We found Bazedoxifene decreased the mRNA expression of IL‐6, MMP2, Col1A1, Col3A1 and periostin in murine hearts after 8‐week surgery. By Western blot detection, we found Bazedoxifene exhibited an inhibition of STAT3 activation in mice three hours and 8 weeks after TAC. Acute TAC stress (3 hours) led to down‐regulated ratio of LC3‐Ⅱ/LC3‐Ⅰ, while in mice after long‐term (8 weeks) TAC this ratio becomes higher than that in Sham mice. Bazedoxifene inverted the autophagic alteration induced by TAC at both two time‐points. In H9c2 myoblasts, Bazedoxifene suppressed the IL‐6‐induced STAT3 activation. Moreover, IL‐6 reduced the ratio of LC3‐Ⅱ/LC3‐Ⅰ, promoted P62 expression but Bazedoxifene reversed both changes in H9c2 cells. Our data suggested Bazedoxifene inhibited IL‐6/gp130 signalling and protected against cardiac remodelling together with function deterioration in TAC mice.